2022
DOI: 10.1038/s41598-022-06598-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative coupling of methane—comparisons of MnTiO3–Na2WO4 and MnOx–TiO2–Na2WO4 catalysts on different silica supports

Abstract: The oxidative coupling of methane (OCM) converts CH4 to value-added chemicals (C2+), such as olefins and paraffin. For a series of MnTiO3-Na2WO4 (MnTiO3-NW) and MnOx-TiO2-Na2WO4 (Mn-Ti-NW), the effect of loading of MnTiO3 or MnOx-TiO2, respectively, on two different supports (sol–gel SiO2 (SG) and commercial fumed SiO2 (CS)) was examined. The catalyst with the highest C2+ yield (21.6% with 60.8% C2+ selectivity and 35.6% CH4 conversion) was 10 wt% MnTiO3-NW/SG with an olefins/paraffin ratio of 2.2. The catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…And although OCM deploys under the reference scenario, its use is dampened in the net-zero scenarios. This is due to the poor conversion efficiency of OCMmodeled here as 30%, which is considered a commercially viable target . Furthermore, in all scenarios, we observe a slow introduction of alternative production technologies, most notably, methanol to chemicals, ODH, and CC.…”
Section: Resultsmentioning
confidence: 94%
“…And although OCM deploys under the reference scenario, its use is dampened in the net-zero scenarios. This is due to the poor conversion efficiency of OCMmodeled here as 30%, which is considered a commercially viable target . Furthermore, in all scenarios, we observe a slow introduction of alternative production technologies, most notably, methanol to chemicals, ODH, and CC.…”
Section: Resultsmentioning
confidence: 94%
“…Effects of TiO 2 , Mn 2 O 3 , and Na 2 WO 4 loadings . For the regular Mn 2 O 3 ‐Na 2 WO 4 /SiO 2 catalyst, many researchers have investigated the effects on catalytic performance of Mn 2 O 3 and Na 2 WO 4 supported on SiO 2 alone or in combination [49,57] . The results of these studies have shown a strong synergy between these components, as the absence of either of them leads to inferior catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…For the regular Mn 2 O 3 -Na 2 WO 4 /SiO 2 catalyst, many researchers have investigated the effects on catalytic performance of Mn 2 O 3 and Na 2 WO 4 supported on SiO 2 alone or in combination. [49,57] The results of these studies have shown a strong synergy between these components, as the absence of either of them leads to inferior catalytic performance. Therefore, the effects of TiO 2 , Mn 2 O 3 , and Na 2 WO 4 loadings on the Mn 2 O 3 -Na 2 WO 4 /SiO 2 -TiO 2 -44 performance were systematically investigated at a GHSV of 10000 mL • g cat.…”
Section: Chemcatchemmentioning
confidence: 99%
“…33 Among the large diversity of catalyst compositions synthesized and tested so far, the strong basic catalysts based on Mo-and La-doped oxides are identified as the most promising ones. 34,35 Selectivity is, however, an issue to be improved as the formation of deep oxidation products (CO x ) is favored by thermodynamics over the production of ethylene. Hence, even though a lot of research has been done with the aim to have suitable catalysts for the reaction, to date, no commerciallly industrially feasible process has been developed.…”
Section: Chmentioning
confidence: 99%
“…Developing a suitable catalyst for the reaction has been a challenge as it must possess the capacity to activate methane to produce, after breaking the C–H bond, methyl radicals which couple to form ethane and selectively promote the conversion of ethane to ethylene via the oxidative dehydrogenation route . Among the large diversity of catalyst compositions synthesized and tested so far, the strong basic catalysts based on Mo- and La-doped oxides are identified as the most promising ones. , Selectivity is, however, an issue to be improved as the formation of deep oxidation products (CO x ) is favored by thermodynamics over the production of ethylene. Hence, even though a lot of research has been done with the aim to have suitable catalysts for the reaction, to date, no commerciallly industrially feasible process has been developed …”
Section: Methanementioning
confidence: 99%